Treating Women Who Are Pregnant and Parenting for Opioid Use Disorder and the Concurrent Care of Their Infants and Children: Literature Review to Support National Guidance - Klaman, Stacey L. (J Addict Med, 2017)
OBJECTIVES: The prevalence of opioid use disorder (OUD) during pregnancy is increasing. Practical recommendations will help providers treat pregnant women with OUD and reduce potentially negative health consequences for mother, fetus, and child. This article summarizes the literature review conducted using the RAND/University of California, Los Angeles Appropriateness Method project completed by the US Department of Health and Human Services Substance Abuse and Mental Health Services Administration to obtain current evidence on treatment approaches for pregnant and parenting women with OUD and their infants and children. METHODS: Three separate search methods were employed to identify peer-reviewed journal articles providing evidence on treatment methods for women with OUD who are pregnant or parenting, and for their children. Identified articles were reviewed for inclusion per study guidelines and relevant information was abstracted and summarized. RESULTS: Of the 1697 articles identified, 75 were included in the literature review. The perinatal use of medication for addiction treatment (MAT, also known as medication-assisted treatment), either methadone or buprenorphine, within comprehensive treatment is the most accepted clinical practice, as withdrawal or detoxification risks relapse and treatment dropout. Medication increases may be needed with advancing pregnancy, and are not associated with more severe neonatal abstinence syndrome (NAS). Switching medication prenatally is usually not recommended as it can destabilize opioid abstinence. Postnatally, breastfeeding is seen as beneficial for the infant for women who are maintained on a stable dose of opioid agonist medication. Less is known about ideal pain management and postpartum dosing regimens. NAS appears generally less severe following prenatal exposure to buprenorphine versus methadone. Frontline NAS medication treatments include protocol-driven methadone and morphine dosing in the context of nonpharmacological supports. CONCLUSIONS: Women with OUD can be treated with methadone or buprenorphine during pregnancy. NAS is an expected and manageable condition. Although research has substantially advanced, opportunities to guide future research to improve maternal and infant outcomes are provided.